2018
DOI: 10.1007/s12022-018-9560-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of 167 Gene Expression Classifier (GEC) and ThyroSeq v2 Diagnostic Accuracy in the Preoperative Assessment of Indeterminate Thyroid Nodules: Bivariate/HROC Meta-analysis

Abstract: The objective of this meta-analysis was to evaluate the performance of the Gene Expression Classifier (GEC) and ThyroSeq v2 (ThyroSeq) in the preoperative diagnosis of thyroid nodules with indeterminate fine-needle aspiration biopsy results. We searched literature databases from January 2001 to April 2018. The bivariate model analysis was performed to estimate pooled sensitivity, specificity, positive likelihood ratio (LR+), negative likelihood ratio (LR−), positive predictive value (PPV), and negative predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…There are some genetic studies for presurgical differentiation of Bethesda classes III and IV to avoid the need for diagnostic surgery [26][27][28]. Due to the high sensitivity and accuracy, genetic analysis may be helpful in ruling out malignancy in cases of indeterminate nodules.…”
Section: Discussionmentioning
confidence: 99%
“…There are some genetic studies for presurgical differentiation of Bethesda classes III and IV to avoid the need for diagnostic surgery [26][27][28]. Due to the high sensitivity and accuracy, genetic analysis may be helpful in ruling out malignancy in cases of indeterminate nodules.…”
Section: Discussionmentioning
confidence: 99%
“…20 A recent meta-analysis reported a pooled Se of 98%, NPV of 91%, Sp of 12% and PPV of 45% for GEC in indeterminate nodules (including class III and IV nodules). 21 A "Rule In" test based on gene sequencing assay, the ThyroSeq has also been evaluated for this purpose. The clinical validation study showed that ThyroSeq v2.1 had a Se, Sp, PPV and NPV of 90.9%, 92.1%, 76.9% and 97.2%, respectively, in nodules with cytological categorization as AUS/FLUS and with known histologic outcome.…”
Section: Utility Of Molecular Testing In Aus/flus Cytologymentioning
confidence: 99%
“…22 recent meta-analysis comparing ThyroSeq v2 with Afirma GEC demonstrated thatThyroSeq v2had a significantly higher Sp and accuracy then GEC. 21 The current version, ThyroSeq v3, analyzing 112 genes was found to have a Se of 93.9% and NPV of 97% in the validation studies for indeterminate cytology and hence, is now considered as a "Rule Out" test. 23,24 ThyGenX (sequencing of eight genes) coupled with ThyraMIR (analyzing 10 miRNAs) demonstrated a Se of 94%, Sp 85%, PPV of 68% and NPV of 97% in the AUS/FLUS category.…”
Section: Utility Of Molecular Testing In Aus/flus Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a 167 gene expression classifier (GEC) has been proposed as a rule-out test due to relatively high sensitivity (92%) and net present value (93%), as reported in a prospective multicenter study. 19 In addition, relatively low specificity of 167 GEC test (48%-53%) has shown that it could not establish malignancy criteria for indeterminate nodules. Alexander et al 20 reported that the prevalence of 167 GEC benign readings varied among institutions and reached up to 29%, which was not significant.…”
Section: Preoperative Ultrasonographymentioning
confidence: 99%